Determine the optimal ignition timing function based on combustion duration, load and fuel blending ratio of an engine powered with diesel-methanol blends - Thong Duc Hong; Dinh Quang Phan; Son Hoang Do; Long Hoang Duong; Minh Quang Pham; Quan Thien Phan Nghiem (PLoS ONE, 2026)
The study employs AVL Boost software to investigate the effects of different methanol blending ratios (BR) in diesel–methanol mixtures (ranging from 0 to 50%), ignition timings (IT), and combustion durations (CD) on the power and brake specific fuel consumption (BSFC) of a single-cylinder diesel engine under various loads of 85, 70, and 50%. Throughout this study, the term IT refers to the start of combustion of diesel fuel in the combustion chamber. The simulation model is validated by comparing the power and torque simulated results and experimental data, with the discrepancy less than 5%. The optimal ITs for maximum power and minimum BSFC are identified, then predictive models are developed based on these optimal IT values as functions of BR at various engine loads and CDs. The results show that the correlations between the IT, BR, CD, and engine load are linear functions. The ITs that simultaneously deliver peak power output and the lowest BSFC are governed primarily by CD, with the BR exerting a secondary effect; whereas, engine load plays a comparatively minor role. For maximum power, the largest variations in optimal ITs are approximately 15 o CA for CD, 5 o CA for BR, and 4 o CA for load. For minimum BSFC, the corresponding maximum differences are about 15, 5, and 3 o CA for CD, BR, and engine load, respectively. Optimal IT prediction models have been established that can minimize the time and cost associated with engine experimental tests to obtain the lowest BSFC and highest engine power at various CDs, engine loads, and methanol BRs.